An Integrated Evaluation Model of Teaching and Learning - Lu, Yi-Ling; Wu, Chih-Wei (Journal of University Teaching and Learning Practice, 2018)
Knowledge transmission and knowledge construction are two common approaches adopted for teaching and learning in higher education. Applying the two different approaches, this paper developed an evaluation model of teaching and learning, which comprises three main conceptual blocks: teaching, learning and learning assistance. A quantitative survey was utilised, collecting data from the Student Assessment of Learning Gains (SALG) along with the Student Evaluation of Teaching (SET) from 108 randomly selected courses at a university in Taiwan. The results demonstrated an R² value of 0.794. The route between teaching and learning was not statistically significant (t=0.0359), indicating that knowledge is constructed in the mind of the student with learning assistance as the mediator.